Direct Amination of Biomass‐based Furfuryl Alcohol and 5‐(Aminomethyl)‐2‐furanmethanol with NH3 over Hydrotalcite‐derived Nickel Catalysts via the Hydrogen‐borrowing Strategy. Issue 8 (23rd February 2021) - Zhou, Kuo; Xie, Ruihong; Xiao, Meiting; Guo, Darun; Cai, Zhuodi; Kang, Shimin; Xu, Yongjun; Wei, Jinjia
Abstract: A series of hydrotalcite‐derived nickel catalysts were synthesized and employed for the direct amination of biomass‐based furfuryl alcohol with NH3 via the hydrogen borrowing strategy. The effects of the Ni/Al molar ratio and calcination temperature of the NiAl hydrotalcite‐like precursors on the performance of the Nix Al‐CT catalyst were investigated. The systematic characterization showed that the synergistic catalysis of the metal and acid‐base sites was of vital importance for the amination of alcohols. In particular, the Ni2 Al‐600 catalyst with high amount of Ni 0 sites (1.26 mmol g −1 ) and suitable density of acid‐base sites (0.71 mmol g −1 and 1.10 mmol g −1, respectively) exhibited the best dehydrogenation capability and therefore excellent catalytic activity. An 84.1 % yield of furfurylamine with complete conversion of furfuryl alcohol was obtained under the reaction conditions of 180 °C and 0.4 MPa NH3 in 36 h. The presence of Ni3 N in the spent catalyst, confirmed by XRD, TEM and XPS characterizations, was demonstrated to be responsible for the deactivation of the Nix Al‐CT catalyst. In addition, the Ni2 Al‐600 catalyst exhibited satisfactory performance toward another important biomass‐related transformation of 5‐(aminomethyl)‐2‐furanmethanol to 2, 5‐bis(aminomethyl)furan, with a yield of 70.5 %. Abstract : Hydrogen borrowing : An efficient NiAl hydrotalcite‐derived nickel catalyst has been developed for the direct amination of biomass‐based furfuryl alcohol and 5‐(aminomethyl)‐2‐furanmethanol with NH3 via the "hydrogen borrowing" strategy. The synergistic catalysis of Ni 0 and Al δ+ ‐Al‐O δ− site was of vital importance for the amination of alcohols into corresponding primary amines.